Avaliação da qualidade de vida em adolescentes com enxaqueca - Paschoal, Joelma Karin Sagica Fernandes [UNIFESP] (2011)
Purpose: To assess the quality of life of adolescents with episodic migraine and chronic, and investigate its relation with the same comorbidities, including sleep disorders, depression and anxiety. Methods: To determine the degree of impact on quality of life of individuals through the use of specific questionnaires to assess quality of life and comorbidities. The diagnosis of headache was established according to the diagnostic criteria of International Headache Society. The statistical analysis was performed comparing the migraine diagnosis, comorbidities and controls, correlating with the quality of life of individuals. Results: 120 subjects were evaluated. Of this total, 13 were excluded. The 107 remaining subjects were in accordance with the criteria for inclusion in the study. Among them, 50 (46%) patients had episodic migraine and 57 (53%) from chronic migraine. Also were interviewed 51 healthy adolescents considered as normal controls. It was observed that adolescents suffering from migraine have a lower quality of life compared to controls. The adolescents with chronic migraine showed significantly lower mean scores in quality of life compared with patients with episodic and higher rates of comorbidities such as depression and trait anxiety. Conclusions: The results point to a negative impact of migraine on quality of life of the patient. The observation of chronic migraine patients reporting the lower scores for quality of life, besides the higher rates of depression and anxiety, is in good agreement with previous studies in the literature. Research to identify precisely the degree of impairment in physical, mental and social life of patients with migraine are fundamental to understanding and developing therapeutic strategies aimed at reducing negative this link.